Improving Multi-Airport Capacity Utilisation in the Veneto Region in Italy - Rotondi, Sebastiano (Cranfield University, 2025)
Multi-airport systems and their effective development can become a mechanism through which growing traffic can be accommodated and allocated as to maximise offering and capacity utilisation. The aim of this research is that of analysing the case study of the Veneto region and its three main commercial airports: Venice Marco Polo, Venice Treviso, and Verona Villafranca. This analysis arises following the loss of a coordinated plan for the traffic allocation across the three airports after the global Covid-19 pandemic. Whilst Venice and Verona are undergoing infrastructural expansion to accommodate future traffic requirements, Treviso had its expansion plans blocked due to noise and emission concerns. Simultaneously, the low-cost traffic that once was handled primarily by Treviso, has now grown and spread across all three airports leading to significant overlap in both the destinations served and carriers handled. This presents an inefficiency and a risk to the system’s capacity both at an airport and airspace level. Therefore, it is required to evaluate the airport system and assess potential optimisation solutions to improve capacity usage and prepare the airports for the future. To understand a possible future, a new traffic forecast was required to analyse hypothetical future scenarios that envisioned the co-existence of the three airports. These scenarios appraised differing traffic distributions in each airport and established that it is no longer possible to allocate traffic to each airport solely by carrier type (low-cost, full-service). The results also suggest that despite there being sufficient capacity for future travel demands, there is a need for a rationalisation of the network and for non-aviation investments like intermodal transport. This optimisation would allow for future organic growth without compromising current infrastructure investments as well as increase value- creation for all airport stakeholders.
Keywords: Multi-Airport System; Italy; Air Traffic Distributions; Traffic Forecasting; Air Traffic Demand